SERBUK BABAKAN BAKAU SEBAGAI PEREKAT PAPAN PARTIKEL - Suwardi Sumadiwangsa (Pusat Penelitian dan Pengembangan Hasil Hutan, 1985)
This experiment evaluate the use of mangrove (Rhizophora mucronata) bark powder mixed with paraformaldehyde as an adhesive in particleboard manufacturing. The treatments consisted of powder size (100 and 140 mesh) and pressing temperature (110,125, and 140° C). The qualities observed were physical and mechanical properties of the boards.The effect of powder size on the properties of particleboard was negative. The effect of temperature on the properties of particleboard was on the other hand significant. There is a linear correlation between temperature and each property of particleboard. Except Thickness Swelling, all properties conform with Particleboard Standard issued by FAO (1966), especially at temperature 125° C or above.